Overview of MRV for the rice sector - Nelson, Katherine (International Rice Research Institute, 2024)
Rice production is crucial for global food security but also a significant source of methane emissions, contributing to climate change. Many countries have incorporated GHG emissions reduction from rice production into their long-term national mitigation and green growth strategies, including their Nationally Determined Contributions (NDCs). Transparent Monitoring, Reporting, and Verification (MRV) is essential for tracking progress toward emission reduction targets, supporting the implementation of national mitigation plans, unlocking climate finance, and producing verified, responsible carbon credits. This presentation explores various MRV methodologies, including empirical estimations, biogeochemical models, and remote sensing technologies. It highlights the strengths and limitations of both national-level and project-level MRV approaches, underscoring their roles in national GHG inventories and project-based verified emission reductions. The discussion will emphasize the need for continuous improvement in MRV systems to enhance accuracy, transparency, and effectiveness in driving low-emission rice production.